ANALISIS TINGKAT KEPUASAN KONSUMEN DI RESTORAN LUMBUNG KAWANUA MANADO - Agus S. Sitepu; Joachim N.K. Dumais; Noortje M. Benu (AGRI-SOSIOEKONOMI, 2021)
The objective of this research is to measure the level of customer satisfaction of restaurant Lumbung Kawanua Manado viewed from the aspect of product, price, place, promotion and service. This research was conducted from September to October 2020, using primary and secondary data with sampling technique of accidental sampling method and respondents were 40 people. The method of analysis used is descriptive data analysis depicting Level of Consumer Satisfaction at Restaurant Lumbung Kawanua Manado. To measure the Level of Consumer Satisfaction at Restaurant Lumbung Kawanua Manado, use the Likert Scale. The result of the research showed that the perception index of customer satisfaction to Restaurant Lumbung Kawanua Manado was 85.6% and classified as very satisfied (SP). Keywords: Analicis, Satisfaction Le